2018
DOI: 10.1088/1674-1056/27/9/097102
|View full text |Cite
|
Sign up to set email alerts
|

Site preferences of alloying transition metal elements in Ni-based superalloy: A first-principles study

Abstract: Atomistic characterization of chemical element distribution is crucial to understanding the role of alloying elements for strengthening mechanism of superalloy. In the present work, the site preferences of two alloying elements X-Y in γ-Ni of Ni-based superalloy are systematically studied using first-principles calculations with and without spin-polarization. The doping elements X and Y are chosen from the 27 kinds of 3d, 4d, 5d group transition metals (Sc,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They also concluded that the so-called "rheniumeffect" cannot be the result of Re clustering and proposed that single Re atom is responsible for the strengthening effect. Lu et al [16] calculated the binding energy of Re-Re pairs, and the study showed that the second nearest neighbor Re-Re pair in γ-Ni phase is more stable under 0 K. Ding et al [17] studied the origin of Re effect on improving the mechanical properties of Ni-based superalloys. They demonstrated that the Re atoms tend to form Cottrell atmosphere at the interfacial dislocation core and stabilize the interfacial dislocation networks.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that the so-called "rheniumeffect" cannot be the result of Re clustering and proposed that single Re atom is responsible for the strengthening effect. Lu et al [16] calculated the binding energy of Re-Re pairs, and the study showed that the second nearest neighbor Re-Re pair in γ-Ni phase is more stable under 0 K. Ding et al [17] studied the origin of Re effect on improving the mechanical properties of Ni-based superalloys. They demonstrated that the Re atoms tend to form Cottrell atmosphere at the interfacial dislocation core and stabilize the interfacial dislocation networks.…”
Section: Introductionmentioning
confidence: 99%
“…The currently popular theoretical method to calculate the site substitution behavior in ordered compounds is first-principles density functional theory (DFT) calculations using the Wagner-Schottky model. [13,14,18,[26][27][28][29][30][31] By adopting this method, our previous calculations [29] of the site occupancy of TM elements in Ni 3 Al indicated that the site behaviors of Fe, Co, Cu, Zn, Ru, Rh, Ag, Cd, and Ir are strongly related to the alloy composition at T = 0 K.…”
Section: Introductionmentioning
confidence: 99%